GENDER JUSTICE IN THE BIBLE - Gurudas, James (Journal of Dharma, 2004)
The very discussion on gender justice in the Bible presupposes suspicion and accusation of injustice to women, caused or perpetuated by the Scripture. Christianity, like any other organized religion, considers its sacred Scripture as its normative basis. Scriptural fundamentalism, which sticks to literal understanding and interpretation of its words, has certainly been detrimental to the cause of women throughout the history of the Church.